Perencanaan Kebutuhan Bahan Baku Produk LM-Hamburger Bun Jempol dengan Metode Material Requirement Planning - Yevita Nursyanti; Rizky Ramadhan (JIEMS (Journal of Industrial Engineering and Management Systems), 2019)
This research aims to determine the planning of raw material requirements for LM-Hamburger Bun Jempol product at PT. Lotte Shopping Indonesia. This research uses Material Requirement Planning (MRP) method with Silver-Meal, Least Total Cost (LTC), and Least Unit Cost (LUC) techniques to calculate the optimal lot size, reorder point time and calculate the smallest total order costs and holding costs. The observation period was carried out for three months, starting from February to April 2018. The data used in this research were product demand data from February to April 2018, and raw material inventory data at the end of April 2018. Comparison of the three techniques it is based on the smallest total inventory costs. The results of these comparisons have been found which have the lowest total cost of the LTC technique of Rp. 17,220,819 while the total cost with Silver-Meal technique is Rp. 17,289,584, and with the LUC technique amounting to Rp. 18,386,458. Therefore, the LTC technique is more economical than the LUC and Silver-Meal techniques because it has the smallest total cost.